Heterogeneous Effects of Urban Land Titling: A Replication of 'Property Rights for the Poor'. Issue 5 (4th May 2019) - Whitney, Edward M.; Cameron, Drew B.; Winters, Paul C.
Abstract: We replicate the analysis of Sebastian Galiani and Ernesto Shargrodsky's (GS) influential 2010 article 'Property rights for the poor: effects of land titling'. GS use a natural experiment in a poor urban area of Buenos Aires to find that land titling increases housing investment, reduces household size, and increases child education, but does not do so through increased use of credit. The original questionnaires and raw data are not available and the existing variables provided by GS allow only a limited replication analysis. Despite these limitations, we successfully reproduce the original findings published by GS, and find these results are robust to alternative specifications. We also find heterogeneous effects regarding gender and education level of the original squatter.